(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the sources of energy generation, which are renewable and non-renewable energy sources, then develop theoretical concepts for the dimensions of sustainable development, address the INTOSAI guide GUID5202, and then prepare a report on the results of auditing the impact of energy sources in achieving sustainable development according to the economic, social and environmental dimensions. The research tools are data and reports issued by the World Bank, the Central Bureau of Statistics and Information, and the Federal General Budget Law of the Republic of Iraq. The research reached a set of conclusions, the most important of which is the decrease in the alternative and nuclear energy index as a percentage of total energy use, and reliance on fossil fuels, which causes an increase in emissions. Greenhouse gases that lead to failure to achieve Goals (2,10,11,12,13,14,15) as well as failure to achieve Goal (7) to ensure everyone’s access at an affordable cost to Modern, reliable and sustainable energy services. The most important recommendations of the research are the necessity of preparing a report on the results of energy indicators and comparing them with what should be according to INTOSAI GUID 5202, to demonstrate the impact of the results of these indicators on the sustainable development goals according to their dimensions.